Exploring predictors of e-marketing continuance intention in the Zimbabwean pharmaceutical industry during the COVID-19 pandemic - Aigbogun, Osaro; Matinari, M.; Fawehinmi, O. (2023)
Purpose: The purpose of this study is to empirically explore the predictors of e-marketing use continuance intention in the pharmaceutical business to business (B2B) supply chain during the COVID-19 pandemic. Design/methodology/approach: This study adopted survey research strategy, and data were collected from managers dealing with marketing in 127 pharmaceutical firms in Harare Zimbabwe using a self-reported questionnaire. Partial least squares structural equation modeling (PLS-SEM) was employed to test the hypotheses. Findings: Leadership support and perceived usefulness are significant predictors of e-marketing continuance intentions. The effect of perceived susceptibility and perceived severity on e-marketing use continuance intention was not significant. Perceived usefulness is a positive moderator in the relationship among leadership support, perceived susceptibility and e-marketing use continuance intention. However, the moderating effect of perceived usefulness created a significant but negative relationship between perceived severity and e-marketing use continuance intention. Originality/value: This study provides empirical evidence of the moderating role of perceived usefulness in the relationships between e-marketing continuance intention and its predictors.